Organizational Culture Transformation in the New Public Management Era: Case Study of Implementation in Indonesian Local Government - Ihyauddin, Ihyauddin; Adi, Bambang Tri Sasongko; Sukmana, Oman; Soedarwo, Vina Salviana Darvina (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The main objective of this study is to understand and evaluate the results of the implementation of New Public Management on the transformation of organizational culture in local government. Methodology: This study uses a qualitative approach. The research design used is a case study design. The population in this study includes local government employees involved in the implementation of NPM and organizational culture transformation. Sample selection was carried out through purposive sampling techniques. Main Findings: The findings show a cultural shift from procedure-oriented to outcome-oriented, supported by decentralization of decision-making and increased employee participation. However, resistance to change and resource constraints remain significant challenges. The study highlights leadership commitment, effective communication, and locally tailored policies as critical factors in successful transformation. Novelty/Originality of this study: This research contributes to the public management literature and offers practical insights for improving the quality of public services.